Unveiling the anticancer potential of Curcuma amada rhizome extract against prostate cancer through computational and experimental approaches - Arpita Priyadarshini; Debajani Mohanty; Swagat Mohanty; Rout George Kerry; Ambika Sahoo; Biswabhusan Dash; Pratap Chandra Panda; Sanghamitra Nayak; Asit Ray; Sudipta Jena (Scientific Reports)
Abstract Prostate cancer (PCa), a common urinary malignancy, is the leading cause of mortality and morbidity among men worldwide. Curcuma amada extract has demonstrated antitumor properties in preclinical models of various cancers, however, its mechanisms against prostate cancer remain unclear. The current study aims to investigate the underlying mechanism of C. amada rhizome extract (CARE) in treating PCa through network pharmacology, bioinformatics analysis and in-vitro experiments. UHPLC-QTOF-HRMS/MS detected 16 phytoconstituents in C. amada, with 15 constituents passing drug-likeness criteria. Public databases identified 1,311 CARE and 473 PCa related targets, with 59 overlapping targets. PPI analysis revealed P53, CTNNB1, EGFR, AKT1, ESR1, HIF1A, CCND1, PIK3CA, and BCL2 as hub targets. Further,4-hydroxycinnamic acid, 13-hydroxylabda-8(17),14-dien-18-oic acid, labda-8(17),12-diene-15,16-dial, zederone, zedoarondiol, zerumin A and caffeic acid were identified as core compounds with high degree values. GO and KEGG analysis identified targets primarily associated with apoptosis and PI3K-AKT signalling pathway. Molecular docking confirmed good binding potential of core compounds with key hub targets, while molecular dynamics (MD) simulation validated the stability of these interactions with minimal fluctuations throughout the simulation. Additionally, mRNA expression levels, immune infiltration and genetic alteration of the hub targets were analyzed. CARE significantly inhibited the proliferation of PC-3 cells, induced apoptosis, and caused G2/M phase arrest. In addition, qRT-PCR analysis revealed that CARE was able to suppress mRNA expression of genes involved in the PI3K-AKT signalling pathway. Thus, the study highlights the underlying mechanism of CARE as a promising treatment option for prostate cancer.